The Origin of Office Documents of Soltis, Peter, Racibor Wojcechowicz and Three Representatives of Ancestry Odrowąż for the Cistercian Monastery in Mogiła from the Years 1228–1231 - Wałkówski, Andrzej (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The objects of interest are three documents of the Monastery of Cistercian in Mogiła exposed byrepresentatives of Lesser Poland medieval elite. The first of them was edited by Cracow soltis (villageadministrator; commune leader), Peter, selling to Cistercians Monastery in Mogiła the village Trusinówfor 50 forfeits of silver in Cracow on May 21st, 1228. The second was exposed by Racibor Wojciechowiczin connection with sale (by reason of ) to Cistercians in his village Zrasowa for 40 forfeits, on May24th, 1230. The third was edited by Szaweł, the Court, the sons of Dobiesław Prandocic Odrowąż, andDobiesław, the son of Wisław Prandocic Odrowąż which together with other relatives waived their rightsto Mogiła, Prandocin, and Mikułowice, previously given to the monastery by Wislaw and Iwo Odrowąż.This document was exposed on September 17th 1231.We are interested in the place of preparation of these three documents. It’s about the question ofwhether and to what extent they were created in the monastery scriptorium. Also to determine the editorialprovenance the editorial office of documents and clarify whether we are dealing with the dictates ofthe Cistercian scriptorium? What are the stylistic features of the text that can speak for this? Do you findthem in the diplomas of other exhibitors for the Cistercian Abbey at the Mogiła, and to which formulasthey refer to? Comparing their style we will establish whether the three documents of Mogiła, which arethe subject of research papers, can be edited in a Cistercian monastery scriptorium, at the Mogiła. Furtherconsiderations concern the writing. You have to answer the question if the vista of searched documentspresent the school of monastic scriptorium and if it is evident in other diplomas of the monastery? Theanalysis of design and writing of these three documents revealed that they were edited and written onpurely in the monastery scriptorium.